2004
DOI: 10.1111/j.1523-1755.2004.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of arteriovenous fistulas in home hemodialysis patients

Abstract: A multidisciplinary approach has been successful in providing durable AV fistulas for home HD for >95% of consecutive patients entering our program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…Before having HD treatment, the patient must go through a surgical access known as anastomosis, which returns the purified blood through a thin fiber after filtering out the waste fluid. The anastomosis is done a few weeks or months before HD treatment and it is done on patient’s elbow or wrist using the non-dominant arm [ 3 , 4 , 5 ]. There are three types of vascular access which are well known in HD treatment, namely Arteriovenous Fistula (AVF), Arteriovenous Graft and Venous Catheter respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Before having HD treatment, the patient must go through a surgical access known as anastomosis, which returns the purified blood through a thin fiber after filtering out the waste fluid. The anastomosis is done a few weeks or months before HD treatment and it is done on patient’s elbow or wrist using the non-dominant arm [ 3 , 4 , 5 ]. There are three types of vascular access which are well known in HD treatment, namely Arteriovenous Fistula (AVF), Arteriovenous Graft and Venous Catheter respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study conducted by Kelvin Lynn et al [37] showed that AV fistulas had good long-term survival when accessed frequently during home dialysis, putting fears of premature graft failure to rest.…”
Section: Fistula Usementioning
confidence: 97%
“…La durée moyenne de la formation était de 35 jours (35)(36)(37)(38)(39)(40)(41)(42). Dix patients (83%) ont été installés à domicile.…”
Section: Programme De La Formation Des Patientsunclassified
“…L'abord vasculaire de référence reste la fistule artérioveineuse (FAV) [38]. Il existe une controverse dans la littérature quant à l'augmentation du taux de complications liées aux ponctions répétées en HDQ [ [40,41], alors que deux études nord-américaines retrouvaient le résultat inverse [42,43].…”
Section: Abords Vasculairesunclassified